2021
DOI: 10.3892/etm.2021.10468
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑103a regulates the calcification of vascular smooth muscle cells by targeting runt‑related transcription factor 2 in high phosphorus conditions

Abstract: Vascular calcification, such as atherosclerosis, is a serious complication of chronic kidney disease that is characterized by tunica media calcification, and has gained increasing attention from researchers. The commonly observed association between vascular calcification and osteoporosis suggests a link between bone and vascular disorders. As microRNAs (miRNAs) have a wide range of gene regulation functions, such as cell proliferation, apoptosis, stress and transdifferentiation, the current study aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In vascular calcification, previous studies have shown that several miRNAs could play essential roles in the regulation of VSMC osteogenic differentiation. miR-223-3p may inhibit the osteogenic switch of vascular smooth muscle cells by regulating IL-6/STAT3 signaling 31 , and miR-103a may regulate the calcification of vascular smooth muscle cells by targeting the expression of Runx2 under high phosphorus conditions 32 . In the present study, we showed that miR-17-5p inhibits the TGF-β1-induced osteogenic differentiation of VSMCs by negatively modulating TGF-β RII expression.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular calcification, previous studies have shown that several miRNAs could play essential roles in the regulation of VSMC osteogenic differentiation. miR-223-3p may inhibit the osteogenic switch of vascular smooth muscle cells by regulating IL-6/STAT3 signaling 31 , and miR-103a may regulate the calcification of vascular smooth muscle cells by targeting the expression of Runx2 under high phosphorus conditions 32 . In the present study, we showed that miR-17-5p inhibits the TGF-β1-induced osteogenic differentiation of VSMCs by negatively modulating TGF-β RII expression.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of miR-103-3a is important as it is able to protect cardiomyocytes from apoptosis and autophagy under hypoxia/reoxygenation by suppressing Atg5 expression and disrupting the Bcl-2-Beclin-1 interaction, which is involved in the regulation of autophagy [118]. RUNX2, a transcription factor for osteogenesis, increases its expression in calcified atherosclerotic plaques and plays an important role in vascular calcification [119]. However, He et al found that upregulation of miR-103a is able to reduce the expression of RUNX2, indicating the important function of this miRNA in preventing calcification in blood vessels [119].…”
Section: Microrna Dysregulation In Postpartum Women Exposed To Pre-ec...mentioning
confidence: 99%
“…RUNX2, a transcription factor for osteogenesis, increases its expression in calcified atherosclerotic plaques and plays an important role in vascular calcification [119]. However, He et al found that upregulation of miR-103a is able to reduce the expression of RUNX2, indicating the important function of this miRNA in preventing calcification in blood vessels [119].…”
Section: Microrna Dysregulation In Postpartum Women Exposed To Pre-ec...mentioning
confidence: 99%
“…Furthermore, microRNAs (miR) possess the ability to control cell growth, death, stress response, and transformation. They also significantly impact the calcification process and the differentiation of VSMCs into osteoblasts in the thoracic aorta of rats [ 9 ]. miR-195-5p was found to be aberrantly expressed in CKD patients with VC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%